Heteroatom-doped nanoporous carbon initiated from bimetallic molecular framework micro-rods for supercapacitor electrodes. Issue 31 (4th June 2019) - Wang, Qiang; Liang, Hongwei; Wu, Dun
Abstract : Zinc and cobalt bimetallic-organic-framework (BMOF) crystalline micro-rods are able to be constructed instantly with the eco-friendly glutamate ligand and building unit of double metallic ions. Abstract : We report herein that zinc and cobalt bimetallic-organic-framework (BMOF) crystalline micro-rods are able to be constructed instantly with the eco-friendly glutamate ligand and building unit of double metallic ions. After carbonization and acid leaching of these precursors, the resultant heteroatom-doped porous carbon occupies not only the enriched mesopore architectures but the ultrathin graphitic networks. Moreover, due to cyclizing dehydration reaction of the glutamate ligand upon thermal conversion, the predominant pyrrolic and pyridinic nitrogen atom sites within the carbon lattices are achieved. The supercapacitor electrodes from these carbonaceous materials without any conductive addictive deliver an impressive specific gravimetric capacitance of 230 F g −1 and a specific areal capacitance of 50 μF cm −2 at a current density of 1 A g −1 in alkaline aqueous electrolyte.